The association of systemic low-grade inflammation with health-related quality of life in Finnish young men - Alho, Mika (2019)
Background During the last two decades, it has become evident that inflammatory mechanisms have central role in pathological processes of several chronic diseases such as type 2 diabetes, cardiovascular disease, stroke, tumorigenesis, chronic obstructive pulmonary disease, and Alzheimer disease. Chronic diseases tend to lower health-related quality of life (HRQoL). Low HRQoL has been associated with increased mortality risk. Several factors like age, gender, body mass index, smoking, cardiovascular fitness, and morbidities have been associated both inflammatory markers and HRQoL. There is a data that HRQoL has been associated inversely with inflammatory markers, but the data is very limited in healthy, young, adult population.